Robust Laser‐Induced Graphene‐Boron‐Doped Diamond Nanowall Hybrid Nanostructures with Enhanced Field Electron Emission Performance for Microplasma Illumination Devices - Mohsen Khodadadiyazdi; Mateusz Ficek; Maria Brzhezinskaya; Shradha Suman; Salila Kumar Sethy; Kamatchi Jothiramalingam Sankaran; Bartłomiej Dec; Mattia Pierpaoli; Sujit Deshmukh; Miroslaw Sawczak; William A. Goddard III; Robert Bogdanowicz (Small Science)
This investigation introduces a scalable fabrication method for laser‐induced graphene (LIG)‐boron‐doped diamond nanowall (BDNW) hybrid nanostructures, designed for field electron emission (FEE) cathode materials in microplasma illumination (μPI) devices. The two‐step process involves fabricating BDNWs via microwave plasma‐enhanced chemical vapor deposition, followed by drop‐casting BDNW dispersion onto polyimide foils to create LIG‐BDNW hybrid nanostructures. Topographic studies reveal that BDNWs on LIG boosts surface area and prevent graphene restacking. High‐resolution transmission electron microscopy confirms precise BDNW decoration, creating sharp edges and high porosity. The effects of boron and nitrogen dopants, highlighted by Raman spectroscopy, are corroborated by near‐edge X‐ray absorption fire structure and X‐ray photoelectron spectroscopies. The hybrid nanostructures exhibit high electrical conductivity and superior FEE properties, with a low turn‐on field of 2.9 V μm−1, a large FEE current density of 3.0 mA cm−2 at an applied field of 7.9 V μm−1, and a field‐enhancement factor of 5,480. The hybrid nanostructures demonstrate an exceptionally low breakdown voltage of 320 V and a plasma current density of 9.48 mA cm−1 at an applied voltage of 550 V. Ab‐initio calculations of the electronic structure further support the experimental findings of these diamond–graphene hybrids, underscoring their potential in advanced electronic applications.